2020
DOI: 10.21744/irjmis.v7n6.997
|View full text |Cite
|
Sign up to set email alerts
|

Time budget pressure on audit quality with audit structure, independence, and audit supervision as moderating variable

Abstract: The audit quality of the public accounting firm / KAP was questioned as there were several cases of fraud, irregularity, and other unhealthy accounting practices that linked several public companies that had been audited and obtained an unqualified opinion / WTP. Empirical research shows that time budget pressure has an effect on audit quality but is not linear because moderating factors are suspected, including time budget pressure, audit structure, independence, and audit supervision. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…However, Reid et al (2019) found this relation between the KAMs and the audit cost insignificant; they mention in the limitation that the auditor may have borne some additional costs related to the new standards but did not pass along these costs to the firm as audit fees. Previous literature argues that the pressure on the auditor may also increase audit fees (Jati and Suprasto, 2020). So, the firm management will pay a cost for adopting the KAMs.…”
Section: Key Audit Mattersmentioning
confidence: 99%
“…However, Reid et al (2019) found this relation between the KAMs and the audit cost insignificant; they mention in the limitation that the auditor may have borne some additional costs related to the new standards but did not pass along these costs to the firm as audit fees. Previous literature argues that the pressure on the auditor may also increase audit fees (Jati and Suprasto, 2020). So, the firm management will pay a cost for adopting the KAMs.…”
Section: Key Audit Mattersmentioning
confidence: 99%
“…This means that there is a linear relationship between the leadership and organizational culture in influencing individual behavior. This is the reason why organizational culture can be categorized as a derivation of subjective norm constructs in TPB theory (Kustina et al, 2019;Jati & Suprasto, 2020;Sanjaya Adi Putra, & Dwirandra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…First, it improves audit work efficiency and enhances the audit supervision function [25]. The internal governance structure and its independence affect auditing effect [42][43][44][45]. This reform has changed the internal governance structure by strengthening the direct leadership of higher-level audit institutions over lower-level audit institutions, thus facilitating the strategic allocation of audit resources and the consolidation of audit capacity.…”
Section: Vertical Management Auditing Reform and Carbon Productivitymentioning
confidence: 99%